Kecemasan Remaja Putri Dalam Menghadapi Nyeri Haid (Dismenorhea) Pada Siswi Kelas VII Di SMPN 1 Mojoanyar Kabupaten Mojokerto - Umi Nadliroh (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2013)
At the time of menstruation, women may experience pain. The nature and level of pain varies, ranging from mild to severe. Menstrual pain usually arising from menars, in the months or the first years of menstruation. Common in the age of 12-15 years. The study was conducted to Know anxiety in the face of young women with menstrual pain (Dismenorhe) in grade VII in SMP 1 Mojoanyar Mojokerto district. This type of study is dekriptif. Variables of anxiety in the face of young women with menstrual pain (Dismenorhe). The population in this study were all over VII grade student who was menstruating at SMPN 1 Mojoanyar Mojokerto district as many as 85 people with purposive sampling techniques sampling obtained a sample of 32 respondents. The instrument used was questionnaire. Based on the results of research in SMPN 1 Mojoanyar - Mojokerto obtained most of the young women respondents (68.8%) had mild levels of anxiety. Anxiety experienced by the young women in menstruation because they have never received information about menstruation so they do not know what they should do in a change in him. The study is expected to be fed to the young women who have Dismenorhe at the time of menstruation.